Clinical complications, monitoring and management of perioperative mild hypotermia: anesthesiological features - Putzu, M.; Casati, A.; Berti, et al., M. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim of the work: Perioperative hypothermia is a frequent occurrence and can lead to several complications, which adversely affect the patient’s outcome, expecially in high risk patient. Nonetheless, central temperature is not frequently monitored in the clinical routine. The aim of this work is to make the point on complications, monitoring techniques, prevention and treatment of mild perioperative hypothermia. Methods: We reviewed literature on cardiovascular, haemorragic, infectious, and other clinical consequences of mild intraoperative hypothermia, epidemiology and techniques, of temperature monitoring and efficacy of different approaches for the prevention and treatment of mild hypothermia. Results: Cardiovascular, haemorragic and infectious complications are significantly more frequent in hypothermic than in normothermic patients. Elderly and high risk patients are more prone to develop perioperative hypotherma, and are more liable to hypothermia-related complications. The ideal monitoring site has to be chosen considering both the patients characteristics and surgical procedure. Once identified, hypothermia has to be treated and the most effective systems are represented by active forced-air skin warming system. Active prewarming during the preoperative period has been also demonstrated to be efficient in reducing the development of intraoperative hypothermia. Humidification and warming of inspired gases, and warming of intravenous fluids are useful techniques when used in a multimodal approach with active skin warming to maintain perioperative normothermia. Conclusions: All the patient undergoing surgery for more than 30 minutes should receive an accurate temperature monitoring and a correct management for the maintenance of normothermia. Reducing the incidence and severity of perioperative hypothermia has the potential for drastically reducing complication-related costs.